Comparison of prediction accuracy of five different biometric formulas - Uğurlu,Adem (2021)
ABSTRACT Objective To compare the performance of Sanders-Retzlaff-Kraft/Theoretical, Hoffer Q, Barrett Universal II, Kane, and Hill-radial basis function formulas to calculate intraocular lens power in eyes with normal axial length, in terms of predicting target refraction by using partial coherence interferometry technology. Methods Phacoemulsification and intraocular lens implantation were performed in 135 eyes of 135 patients with an axial length between 22 and 24.5 mm. Axial length, keratometry, and anterior chamber depth were measured by intraocular lens Master 500. Sanders-Retzlaff-Kraft/Theoretical, Hoffer Q, Barrett Universal II, Kane, and Hill-radial basis function formulas were used for intraocular lens power calculations. The difference between the expected postoperative refraction and the mean absolute prediction error was calculated for each eye. Statistical significance was evaluated at the level of p<0.05. Results The study included 135 subjects. The mean axial length, anterior chamber depth, keratometry, and intraocular lens power were 23.2±1.2 (22 to 24.5) mm, 3.2±0.4 (2.4 to 4.4) mm, 43.5±1.5 (40.8 to 46.2) diopter, 21.5±1.8 (18.5 to 25.5) diopter, respectively. The mean absolute prediction error for Sanders-Retzlaff-Kraft/Theoretical, Hoffer Q, Barrett Universal II, Kane, and Hill-radial basis function was 0.306±0.291, 0.312±0.257, 0.314±0.268, 0.299±0.206 and 0.308±0.280, respectively (p>0.05). Conclusion The study showed the third-generation (Sanders-Retzlaff-Kraft/Theoretical and Hoffer Q), fourth-generation (Barrett Universal II) and new-generation (Kane and Hill-radial basis function) intraocular lens power calculation formulas had similar performances regarding calculation of intraocular lens power to predict target refraction after phacoemulsification in eyes with normal axial length.